2009
DOI: 10.3844/jssp.2009.452.459
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Critical Knowledge Characteristics on Degree of Inter-Firm Technology Transfer

Abstract: Problem statement:The current issue on inter-firm technology transfer in the developing countries is centered on the efficiency and effectiveness of the transfer process by the Multinationals (MNCs). Thus, organizations in the developing countries are striving hard to collaborate, learn and internalize their foreign partner's technological knowledge by forming strategic alliances or International Joint Ventures (IJVs) as an efficient mean to increase their competitiveness, technological capabilities and potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The MS firms place 'low cost labour' as a contribution of the local partner in the first rank of importance. Sazali et al (2009b) recently pointed out this as an important contribution of the local partner in their study in China. Contrary to that study however, Malaysian MDs were comparing the salaries of highly qualified personnel in the biotechnology area in Malaysia with those salaries offered internationally or in developed countries.…”
Section: Views Of Potential Contributions From the Local Partnermentioning
confidence: 93%
See 1 more Smart Citation
“…The MS firms place 'low cost labour' as a contribution of the local partner in the first rank of importance. Sazali et al (2009b) recently pointed out this as an important contribution of the local partner in their study in China. Contrary to that study however, Malaysian MDs were comparing the salaries of highly qualified personnel in the biotechnology area in Malaysia with those salaries offered internationally or in developed countries.…”
Section: Views Of Potential Contributions From the Local Partnermentioning
confidence: 93%
“…A few publications list potential contributions of partners of joint ventures or alliances: Stopford and Wells (1972); Beamish (1994) and more recently: Geringer (1991); Glaister and Buckley (1997); Sazali et al (2009b); Parkhe (2003); Pan (2004) and Prahalad and Ramaswamy (2004).…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, in the context of cross-cultural technology transfer, much prior quantitative research has investigated the factors inhibiting and facilitating knowledge and technology transfer in cross-cultural business contexts, but these works have covered only a few dimensions, such as the characteristics of the knowledge, the suppliers and recipients, and their relationships (e.g., Rebentisch & Ferretti, 1995;Pak & Park, 2004;Le & Evangelista, 2007;Sazali, Raduan, Jegak, & Haslinda, 2009). Some studies have indicated the importance of national culture in the cross-cultural knowledge transfer process (e.g., Simonin, 1999;Holden, 2002;Pauleen, Wu, & Dexter, 2007).…”
Section: Relevant Researchmentioning
confidence: 99%
“…transfer capacity and partner protectiveness) [38]; transferee characteristics (absorptive capacity and recipient collaborativeness) [38]; transfer environmental factors such as, mode of transfer, complexity level, government policy and enforcement; and learning environmental factors such as, relationship quality and mutual trust.…”
Section: B Reviewing the Factors Affecting Itt Performance Through Tmentioning
confidence: 99%